EFIKASI DIRI DAN KECERDASAN ADVERSITAS SEBAGAI FAKTOR KARAKTERISTIK KEPRIBADIAN YANG BERPENGARUH TERHADAP INTENSI BERWIRAUSAHA MAHASISWA - Herwiek Diyah Lestari Herwiek; Ratna Pujiastuti (FEB UNWIKU PURWOKERTO, 2021)
This study aims to analyze the effect of self-efficacy and adversity quotient as factors of personality characteristics on students' entrepreneurial intentions. This research was conducted on students of the Management Study Program, Faculty of Economics and Business, University of Wijayakusuma Purwokerto. The number of samples used was 56 respondents, and the sampling technique used was purposive sampling method. To determine the sample size using the method developed by Krejcie and Morgan. The analysis tool used is Multiple Linear Regression (Multiple Regression). The t test is used to test the significance of the influence of the variable self-efficacy and adversity quotient, Student Entrepreneurship Intention. The results of the analysis using the level of confidence 95% (α = 0.05) and degree of freedom (df) = (n-k) = (56-3) = 53, the t table is 1.674. The t value for the Self Efficacy variable (th1 = 6,521) with a significance of 0,000 and the t value for the Adversity Quotient variable (th2 = 5,604) with a significance of 0,000. The value of t count> t table with a significance of 0.000 <0.05, so that Ho is rejected. This means that Self Efficacy and Adversity Quotient have a significant positive effect on Entrepreneurial Intention. This shows that the better the Self Efficacy and Adversity Quotient students have, the more students desire the Economics and Business Faculty to be entrepreneurial.